Pediatric liver transplantation using a hepatitis B surface antigen-positive donor liver graft for congenital absence of the portal vein - Jung-Man Namgoong; Shin Hwang; Dae-Yeon Kim; Tae-Yong Ha; Gi-Won Song; Dong-Hwan Jung; Kyung Mo Kim; Seak Hee Oh (Korean Journal of Transplantation, 2021)
Congenital absence of the portal vein (CAPV) is a rare venous malformation in which mesenteric venous blood drains directly into systemic circulation. Herein, we report a case of pediatric deceased donor liver transplantation (DDLT) for symptomatic CAPV with whole liver graft from a hepatitis B surface antigen (HBsAg)-positive donor. A 4-year-old boy suffered from CAPV and secondary portal hypertension. He was also diagnosed with DiGeorge syndrome and heart anomalies. After waiting for 4 months, a 5-year-old donor weighing 19 kg with positive HBsAg was allocated to this 4-year-old patient weighing 15 kg. Recipient operation was performed according to the standard procedures of pediatric DDLT. Portal vein reconstruction was performed using interposition of a vascular homograft conduit to the superior mesenteric vein-splenic vein confluence. The patient recovered uneventfully from DDLT. He has been administered with lamivudine to prevent hepatitis B virus infection. This patient has been doing well for 5 years after DDLT without growth retardation. In conclusion, CAPV patients can have various vascular anomalies, thus combined vascular anomalies should be thoroughly assessed before and during liver transplantation operation. The most effective reconstruction techniques should be used to achieve satisfactory results following liver transplantation.